Increasing the Retirement Age in Intensive Care Medicine: Perception of the Effect on Patient Safety and Personal Health. (January 2014) - Jones, Ami; Walker, Jason; Thorpe, Chris
The government has recently increased the retirement age and as a result doctors are going to have to work longer. Intensive care medicine is a demanding specialty with significant on-call commitment, and this paper looks at the potential ramifications of this policy change on patient safety and personal health of intensivists. All consultants working in Wales with sessions in intensive care medicine were asked to complete a survey to ascertain their opinion on whether increasing age would affect patient safety or their personal health. If asked to work beyond the age of 60, 80% of respondents thought that patient safety would be jeopardised and 67% of respondents felt their personal health would be affected. Twenty-seven respondents (43%) have had or currently have health problems linked with work, and this correlates with the intensity of the on-call (p<0.004). Intensivists have substantial concern about whether increasing the retirement age is a realistic proposition in this specialty. If a consultant feels that he or she is not providing safe care it is important that the problem can be raised and addressed with the full support of the employers and the profession, and without penalty.